The Impact of Financial Literacy on Entrepreneurial Intention: The Mediating Role of Saving Behavior - Alshebami, Ali Saleh; Al Marri, Salem Handhal (Frontiers in Psychology, 2022)
This study explored the impact of financial literacy (financial awareness) on potential entrepreneurs' intent in Saudi Arabia. It also examined saving behavior as a mediator in the relationship between financial literacy and entrepreneurial intention. The study's data were collected by an online questionnaire sent to a sample of 270 potential entrepreneurs at Abqaiq Applied College, affiliated with King Faisal University. Data analysis was done using partial least squares structural equation modeling (PLS-SEM). According to the findings, there is no direct relationship between financial literacy and entrepreneurial intent. However, it has been reported that saving behavior can mediate between financial literacy and entrepreneurial intent.